(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2024)
The major portion of the Nepalese economy is based on agriculture. The country’s rural areas are home to almost 80% of the inhabitants, who are engaged in agriculture. People are compelled or forced to migrate due to a variety of reasons including poverty, desperation, unfair resource distribution, and a lack of opportunity. This study’s major goal is to determine how remittances affect the socio-economic aspects of households both before and after they receive remittances. The Bhadaure, Tamagi village at Ward number 4 of the Annapurna Rural Municipality is the place where the current study was carried out. Only 50 respondents out of 200 migrants working abroad were chosen at random as a sample of the study. The research method was a case study design, the quantitative data were collected using structured questionnaire where SPSS version 20 was used for data analysis. The objective of the study was to identify the impacts of remittances on the expenditure of migrant households and compare the position of remittance holders before and after receiving remittances. The findings of the study highlight the positive impact of remittance on the living standards of households. Many households were able to construct RCC buildings and buy land in which they were previously unable to construct due to financial constraints. There was also an improvement in household assets, electronic goods, and services after receiving remittances. Moreover, the results show that the health conditions of households had improved after receiving remittances. The findings indicate that remittance has a significant impact on the socioeconomic development of the study area, contributing to the improvement of the living standards and well-being of the households. Despite this, the government must ensure protection against labor exploitation and formulate appropriate policies for Nepalese laborers.